2021
DOI: 10.1111/jce.14879
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow volume of left atrial appendage measured by magnetic resonance imaging is improved after radiofrequency catheter ablation of atrial fibrillation

Abstract: Introduction Hemodynamics of left atrial appendage (LAA) is an important factor for future risk of ischemic stroke in atrial fibrillation (AF) patients. Velocity encoded cardiac magnetic resonance imaging (VENC‐MRI) can evaluate blood flow volume of LAA without any invasive procedures. We aimed to evaluate the association between radiofrequency catheter ablation (RFCA) and LAA hemodynamics measured by MRI. Methods and Results Consecutive RFCA cases in a single arrhythmia center were retrospectively analyzed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…LAAFV is regarded as a reliable predictor of AF recurrence because it reflects the comprehensive LAA hemodynamics and the severity of LA remodeling ( 45 ). Similar to the study by Kim et al ( 46 ), we found that patients with decreased LAAFV before ablation were more likely to experience AF recurrence. Therefore, it is reasonable to include these regular predictors in the nomogram.…”
Section: Discussionsupporting
confidence: 90%
“…LAAFV is regarded as a reliable predictor of AF recurrence because it reflects the comprehensive LAA hemodynamics and the severity of LA remodeling ( 45 ). Similar to the study by Kim et al ( 46 ), we found that patients with decreased LAAFV before ablation were more likely to experience AF recurrence. Therefore, it is reasonable to include these regular predictors in the nomogram.…”
Section: Discussionsupporting
confidence: 90%
“…Not all de novo diagnoses of cardiac arrhythmia lead to therapeutic interventions, but still, important clinical decisions can be made. A diagnosis of AF can lead to anticoagulation, if indicated, to prevent ischemic stroke, or RFCA to eliminate AF itself [ 17 , 18 , 19 ]. Detection of PSVT or VT can also lead to successful treatment of the disease via RFCA.…”
Section: Discussionmentioning
confidence: 99%
“…25 26 In addition, the experimental evidence also implied that patients with decreased LAA function prior to ablation are more likely to relapse. 27 LAAFV reflects the comprehensive LA function and severity of LA remodelling and has been considered as a reliable predictor of AFR. 28 GLS measured by STE for the assessment of LA reservoir function has showed its prognostic value in predicting the recurrent of AF, as it provides characterisation and quantification of LA myocardial deformation, including the compliance of the atrial wall as well as myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%